2011
DOI: 10.3390/molecules16108745
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Functionalized Spiropyrrolizidine Oxindoles via a Three-Component Tandem Cycloaddition Reaction

Abstract: An efficient synthesis of functionalized spiropyrrolizidine oxindoles via a three-component tandem cycloaddition has been achieved. This strategy can provide direct and rapid access to spiropyrrolizidine oxindoles in high yields (up to 99%) with excellent diastereoselectivities (up to 99:1 dr). The features of this procedure are the following: mild reaction conditions, high yields, high diastereoselectivities, one-pot procedure and operational simplicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…C and 2D NMR spectroscopy.Liu et al reported a three-component tandem cycloaddition reaction between substituted isatins 114, L-proline 74 and various maleic acid derivatives 157 that led to the racemic spiropyrrolizidine oxindoles 158 (Scheme 36)[93].Scheme 36 Synthesis of racemic spiropyrrolizidine oxindolesMurugan et al reported the cycloaddition of azomethine ylides generated from the decarboxylative condensation of isatin 114 with octahydro-1H -indole-2-carboxylic acid 159 with triarylideneacetylacetone derivatives 160 to obtain novel spiroheterocycles 162 with high regio-and stereoselectivity. The hypothetical product 163 was not detected (Scheme 37)[94].…”
mentioning
confidence: 99%
“…C and 2D NMR spectroscopy.Liu et al reported a three-component tandem cycloaddition reaction between substituted isatins 114, L-proline 74 and various maleic acid derivatives 157 that led to the racemic spiropyrrolizidine oxindoles 158 (Scheme 36)[93].Scheme 36 Synthesis of racemic spiropyrrolizidine oxindolesMurugan et al reported the cycloaddition of azomethine ylides generated from the decarboxylative condensation of isatin 114 with octahydro-1H -indole-2-carboxylic acid 159 with triarylideneacetylacetone derivatives 160 to obtain novel spiroheterocycles 162 with high regio-and stereoselectivity. The hypothetical product 163 was not detected (Scheme 37)[94].…”
mentioning
confidence: 99%
“…Spiropyrrolizine oxindoles are important synthetic targets and several reports of such syntheses exist [3,4]. Such new heterocyclic scaffolds can be prepared by the intermolecular 1,3-dipolar cycloaddition reaction of azomethine ylide with olefinic and acetylenic dipolarophiles [5].…”
Section: Introductionmentioning
confidence: 99%
“…MCRs are of significant importance from the view point of simplicity and its efficiency since the reactions are widely applied in pharmaceutical chemistry for producing different structures and combinatorial libraries for drug discovery [1]. One of the most applicable structures which have become a privileged skeleton with broad and promising activities in various therapeutic areas is spirooxindole compounds [1].Nowadays, enantioselective synthesis of spirooxindoles via efficient catalysts has been developing utilizing novel catalyst systems [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].Bergman at coworkers synthesized various derivatives of mono spirooxindol via one pot reaction of isatin and some alpha-amino acids in methanol and water [17].Also, Yau et al reported the MCR reaction of isatin , pyrolidin, 2-carboxilic acid and molonat esters to furnish spirooxindols in good yieds [18].In addition, Yang and coworkers utilized four-component condensation between aromatic aldehyd , 1,3 indandion, sarcozin and isatin to prepare a series of di spiropirolidin compounds via knovenagol reaction [19].…”
Section: Introductionmentioning
confidence: 99%